Modulation of gut microbiota by Gardeniae Fructus oil exerts TLR4/NF-κB/NLRP3 pathway-mediated antidepressant effects based on transcriptomics and fecal transplantation - Han, Man; Zhou, Yujing; Gao, Xinyu; Cheng, Xixi; Deng, Ling; Ji, Shilin; Li, Zhengheng; Cai, Yu; Yan, Chunchao; Chen, Yunzhong (Frontiers in Pharmacology, 2025)
BackgroundAlthough our team has demonstrated the antidepressant effect of Gardeniae Fructus oil (OGF) in the early stages, the mechanism of whether OGF works by regulating the gut microbiota is not clear. This study aims to elucidate OGF’s gut-brain axis mechanism in depression.MethodsChronic unpredictable mild stress (CUMS) was used to establish a depressed mouse model, and the depression-like behavior of mice was observed by behavioral tests after antibiotic pretreatment and fecal microbiota transplantation (FMT). HE staining was used to observe the pathological changes in the hippocampus and colon; ELISA was used to detect the content of neurotransmitters and pro-inflammatory factors; Western blot was used to detect the expression of colonic tight junction proteins. The signaling pathways regulating the antidepressant properties of OGF were obtained by transcriptome sequencing analysis and validated at the protein level.ResultsCompared with the CON group, mice in the CUMS group showed significant depressive-like behavior, pathological damage to the hippocampus and colon tissues, significant decrease in levels of 5-HT, DA, and BDNF in the hippocampus, significant increase in levels of IL-1β, IL-6, TNF-α, DAO, and LPS in serum, significant decrease in colonic tight junction protein expression, and significant increase in protein expression of TLR4, p-NF-κB, NLRP3, ASC, and IL-1β in the hippocampus (P < 0.01); Compared with the CUMS group, the FMT group could effectively improve the above situation (P < 0.05, P < 0.01), whose therapeutic effect was second only to the OGF group (P < 0.01), while ABX + OGF group did not show obvious therapeutic effect.ConclusionOGF might exert antidepressant effects by modulating gut microbiota and mediating the hippocampal TLR4/NF-κB/NLRP3 pathway.